DAYA SAING KAKAO INDONESIA DI PASAR INTERNASIONAL - Anggita Tresliyana; Anna Fariyanti; Amzul Rifin (School of Business, Bogor Agricultural University (SB-IPB), 2015)
Cocoa is one of the major Indonesian agricultural export products. Cocoa international market has great potential regarding world’s consumption growth, therefore Indonesia is expected to take advantage on existing opportunities. The aims of this study were to analyze the competitiveness of Indonesian cocoa beans and processed cocoa trade in the international market as well as the level of competition between cocoa exporting countries. By using Revealed Comparative Advantage (RCA) and Spearman Rank Correlation, it showed that Indonesia had a comparative advantage as an cocoa exporter on the international market, the highest for cocoa beans and the lowest for cocoa paste; Indonesia also had a significant correlation to exporting countries in cocoa beans’ market (Ghana) and cocoa paste’s market (Netherlands and Malaysia), the correlation suggests that there were high correlation between Indonesia and the exporting country in competing for market share.Keywords: cocoa, comparative advantage, international trade, competitiveness, market share, RCA ABSTRAKKakao merupakan salah satu komoditas pertanian unggulan ekspor Indonesia. Pasar kakao memiliki potensi yang besar dilihat dari peningkatan konsumsi dunia, sehingga Indonesia diharapkan dapat memanfaatkan peluang yang ada. Tujuan penelitian ini adalah menganalisis daya saing perdagangan biji kakao dan kakao olahan Indonesia di pasar internasional serta hubungan daya saing antar negara eksportir kakao. Dengan menggunakan Reavealed Comparative Advantage (RCA), dan Korelasi Rank Spearman, hasil analisis menunjukkan bahwa Indonesia memiliki keunggulan komparatif sebagai eksportir biji kakao dan kakao olahan di pasar internasional, tertinggi untuk biji kakao dan terendah untuk kakao pasta; Indonesia juga memiliki korelasi yang signifikan di beberapa negara untuk pasar biji kakao (Ghana) dan kakao pasta (Belanda dan Malaysia), korelasi tersebut menunjukkan bahwa terdapat hubungan daya saing yang cukup tinggi antara Indonesia dengan negara eksportir tersebut dalam perebutan pangsa pasar dunia. Kata kunci: kakao, keunggulan komparatif, perdagangan internasional, daya saing, pangsa pasar, RCA